A positive analysis of immigration policy - Giorgio Bellettini; Carlotta Berti Ceroni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
This paper studies the determinants of immigration policy in an economy with entrepreneurs and workers where a trade union has monopoly power over wages. The presence of the union leads a benevolent government to implement a high level of immigration and induces a welfare loss not only from an aggregate point of view, but even from the point of view of workers. In the politico-economic equilibrium where interest groups lobby for immigration, we show the condition under which workers are no longer hurt by the presence of the union.
Keywords: 330; Migrationspolitik; Neue politische Ökonomie; Gewerkschaft; Interessenpolitik; Wohlfahrtsanalyse; Theorie